Special Diplomatics Analysis Method: The Application in Correspondence of the Ministry of Health - Çiçek, Niyazi (Information World, 2006)
Diplomatic analysis, which comprises the study on the authenticity of rather inactive records like those of the Ottomans, can also be applied to recent records, and among them the electronic type of records. The study aims at the discussion of principles of special diplomatic analysis, and an exemplification is brought by through a sample application out of the correspondence of Ministry of Health.